COMPARATIVE ANALYSIS OF THE WAHHABI MOVEMENT IN THE MIDDLE EAST AND THE WESTERN BALKANS - Ivana Alcalay; Bjegovic, Miroslav (The Policy of National Security, 2025)
This paper presents a comparative analysis of the Wahhabi movement in the Middle East and the Western Balkans, focusing on the differences in institutional foundations, operational methods, and social consequences. In the Middle East, Wahhabism is an integral part of the political–religious order of Saudi Arabia, enjoying full institutional support from the state, including formal control mechanisms such as the religious police. In contrast, in the Western Balkans, Wahhabism represents an imported ideology without institutional backing, yet with significant influence from foreign actors and transnational networks. Its presence has caused ideological and organisational divisions within local Islamic communities, challenging traditional religious practices rooted in Ottoman heritage and Sufi traditions. Special attention is given to the security implications, including the potential for radicalisation and community destabilisation. The analysis demonstrates that, despite differences in the degree of institutional support and operational methods, Wahhabism in both regions can significantly influence religious dynamics, social cohesion, and security trends.